Targeted muscle reinnervation in the initial management of traumatic upper extremity amputation injury - Cheesborough, Jennifer E. (Springer US, 2014)
Targeted muscle reinnervation (TMR) was initially designed to provide cortical control of upper limb prostheses through a series of novel nerve transfers. Early experience has suggested that TMR may also inhibit symptomatic neuroma formation. We present the first report of TMR performed at the time of a traumatic shoulder disarticulation. The procedure was done to prevent painful neuroma pain and allow for myoelecteric prosthetic use in the future. Eight months post-operatively, the patient demonstrates multiple successful nerve transfers and exhibits no evidence of neuroma pain on clinical exam. Using the Patient Reported Outcomes Measurement Information System (PROMIS), the patient demonstrates minimal pain interference or pain behavior. Targeted muscle reinnervation may be considered in the acute trauma setting to prevent neuroma pain and to prepare patients for myoelectric prostheses in the future.